Effect of the Initial Time of Providing Oat Hay on Performance, Health, Behavior and Rumen Fermentation in Holstein Female Calves - Tianyu Chen; Jianxin Xiao; Tingting Li; Jing Ma; Gibson Maswayi Alugongo; Muhammad Zahoor Khan; Shuai Liu; Wei Wang; Yajing Wang; Shengli Li; Zhijun Cao (Agriculture, 2021)
For determining the appropriate time of feeding hay, 210 healthy Holstein calves at day two were randomly divided into three groups: basic diet (calf starter) without hay (CON), and the inclusion of oat hay from the second week (H2) or fourth week (H4) with basic diet. Calves were weaned on day 56 and raised until day 70. Calf starter intake and fecal scores were recorded daily. The body weight, body size, and rumen fluid samples were collected every two weeks before and once a week after weaning. Compared to the basic diet group, the calves that were receiving oat hay from the second week had the highest starter intake (1086.1 g vs. 925.6 g; p < 0.05), body weight (68.4 kg vs. 63.0 kg; p < 0.01) and average daily gain (0.84 kg/d vs. 0.73 kg/d; p < 0.01) throughout the trial period. Compared to H4, calves received oat hay from the second week reduced the frequency (1.48% vs. 3.57%; p < 0.05) and duration of diarrhea (0.21 days vs. 0.50 days; p < 0.05) during post-weaning. Compared to the CON calves, the inclusion of oat hay from the second week increased the ruminal pH (6.38 vs. 6.19; p < 0.01) during the entire trial and increased the acetate (49.07% vs. 44.44%; p < 0.05) during post-weaning. Compared to the basic diet group, calves in H2 treatment spent more time in rumination (275.2 min/day vs. 133.3 min/day; p < 0.01) but less time in abnormal behaviors (80.5 min/day vs. 207.0 min/day; p < 0.01). In conclusion, calves supplemented with oat hay had an improved growth rate and rumen environment compared to calves fed calf starter only.